Clinical and magnetic resonance imaging features of lymphoma involving the nervous system in cats - Alexane Durand; Erin Keenihan; Daniela Schweizer; Arianna Maiolini; Julien Guevar; Anna Oevermann; Rodrigo Gutierrez‐Quintana (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Lymphoma is the most common spinal cord neoplasm and second most common intracranial tumor in cats, but description of specific magnetic resonance imaging (MRI) features is lacking. Objective Describe the clinical and MRI features of lymphoma affecting the central (CNS) or peripheral (PNS) nervous system or both in cats. Animals Thirty‐one cats with confirmed cytological or histopathological diagnosis or both of lymphoma involving the CNS or PNS or both, and MRI findings of the lesions. Methods Multicenter retrospective descriptive study. Signalment and medical information were recorded. Magnetic resonance imaging findings were reviewed by 3 observers following a list of predefined criteria and consensus was sought. Frequency distributions of the different categorical data were reported. Results Median duration of clinical signs at time of presentation was 14 days (range, 1‐90). Neurological examination was abnormal in 30/31 cats. On MRI, lesions affecting the CNS were diagnosed in 18/31 cats, lesions in both CNS and PNS in 12/31, and lesions in the PNS only in 1/31. Intracranial lesions were diagnosed in 22 cats (extra‐axial, 7/22; intra‐axial, 2/22; mixed, 13/22), and spinal lesions were diagnosed in 12 (6/12 involving the conus medullaris and lumbosacral plexuses). Infiltration of adjacent extra‐neural tissue was present in 11/31 cases. Contrast enhancement was seen in all lesions, being marked in 25/30. Meningeal enhancement was present in all but 2 cases. Several distinct MRI patterns were observed. Conclusions and Clinical Importance Nervous system lymphoma in cats has a wide range of MRI features, of which none is pathognomonic. However, together with clinical data and cerebrospinal fluid (CSF) analysis, MRI may provide a strong tentative antemortem diagnosis.